Gender, role and performer in Athenian theatre iconography: A masked tragic chorus with KALOS and KALE captions from Olbia. (9th December 2014) - Braund, David; Hall, Edith
Abstract: A vase fragment from Olbia has been recognized in recent years as a key piece of evidence for the tragic chorus in fifth-century Athenian drama, especially because it shows the use of masks by dancers in such a chorus. This article provides the first clear illustration of the fragment, revealing much detail about the dress of the dancers, with a range of further information about the object (its size, discovery etc.). The illustration shows for the first time that the scene on the fragment includes inscriptions which declare the central aulete and percussionist to be KALOS and each of the two dancers to be KALE. A survey of KALE tags and similar inscriptions shows that there is no direct parallel for these KALE inscriptions. Moreover, these KALE tags are all the more remarkable in that they are attached to dancers who are appearing in female dress and female roles, but who are also male in biological sex. That usage raises the larger issue of gender in the theatre, which is set beside other indications that actors might be treated as in some sense female.